Ancient-Pathogen Genomics: Coming of Age? - Adrian M. Whatmore (American Society for Microbiology, 2014)
ABSTRACT The potentially debilitating zoonotic disease brucellosis is thought to have been a scourge of mankind throughout history. New work by Kay et al. [mBio 5(4):e01337-14, 2014] adds to evidence for this by exploiting the huge advances in next-generation sequencing technology and applying shotgun metagenomics to a calcified nodule obtained from a 14th-century skeleton from Sardinia. While not the first DNA-based confirmation of Brucella in medieval DNA samples, Kay et al.’s study goes much further than previous reports based on single gene fragments in that it allows a full-genome reconstruction and thus facilitates meaningful comparative analysis of relationships with extant Brucella strains. These analyses confirm the close relationship of the genome to contemporary isolates from the western Mediterranean, illustrating the continuity of this lineage in the region over centuries. The study, along with recent studies characterizing other ancient-pathogen genomes, confirms that shotgun metagenomics offers us a powerful tool to fully characterize pathogens from ancient samples. Such studies promise to revolutionize our understanding of the nature of infectious disease in these materials and of the wider picture of the emergence, evolution, and spread of bacterial pathogens over history.